2022
DOI: 10.3390/antiox11061177
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Melatonin in the Culture Medium Does Not Affect the Development of In Vivo-Derived Pig Embryos but Substantially Improves the Quality of In Vitro-Produced Embryos

Abstract: Cloned and transgenic pigs are relevant human disease models and serve as potential donors for regenerative medicine and xenotransplantation. These technologies demand oocytes and embryos of good quality. However, the current protocols for in vitro production (IVP) of pig embryos give reduced blastocyst efficiency and embryo quality compared to in vivo controls. This is likely due to culture conditions jeopardizing embryonic homeostasis including the effect of reactive oxygen species (ROS) influence. In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 104 publications
2
4
0
Order By: Relevance
“…Overall, current studies support the finding that melatonin may enhance preimplantation embryonic development [67,68,[70][71][72] and the success rate of implantation [68,72], as indicated by human clinical studies and animal research. Furthermore, some studies indicate that melatonin could result in a reduction in ROS during embryo development, and this may lead to a decrease in DNA damage [70,72,73].…”
Section: N-acetyl-5-methoxytryptamine (Melatonin)supporting
confidence: 83%
See 1 more Smart Citation
“…Overall, current studies support the finding that melatonin may enhance preimplantation embryonic development [67,68,[70][71][72] and the success rate of implantation [68,72], as indicated by human clinical studies and animal research. Furthermore, some studies indicate that melatonin could result in a reduction in ROS during embryo development, and this may lead to a decrease in DNA damage [70,72,73].…”
Section: N-acetyl-5-methoxytryptamine (Melatonin)supporting
confidence: 83%
“…The most recent study with in vivo-derived and in vitro-derived porcine embryo examined the effects of the sequential addition of melatonin to the IVM, IVF, and culture medium by development competence [70]. Melatonin accelerated embryo development (p < 0.05), showing a significant increase in the cleavage development rate (p < 0.001) while indicating no notable difference in the blastocyst rate.…”
Section: N-acetyl-5-methoxytryptamine (Melatonin)mentioning
confidence: 99%
“…Despite substantial progress in the field of IVC optimization, in vitro -derived embryos have a lower ratio of early-stage development than in vivo -cultured embryos [ 5 ]. Long-term accumulation of ROS within embryos during the process of IVC has been established as a significant factor altering in vitro embryo quality [ 6 ]. Importantly, OS caused by an imbalance between antioxidants and ROS can negatively affect the efficiency of IVC [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our study also demonstrated that the use of a novel IVM system based on CNP pretreatment considerably enhanced the developmental competence of the bovine oocytes ( Table 2 ), which was due to CNP increased oocytes cGMP levels [ 32 ]. Evidence from numerous studies on humans [ 33 ], bovine [ 26 , 34 , 35 ], and pigs [ 36 , 37 ] has shown that MT supplementation was beneficial for the IVM of oocytes and their development; and, reducing ROS levels depicts why the combination treatment of CNP and MT significantly enhanced the developmental competence of the bovine oocytes. The oocytes treated with CNP, MT, and FLI showed the highest development potential because FLI promoted porcine oocyte IVM by activating MAPK1/3 [ 19 , 38 ].…”
Section: Discussionmentioning
confidence: 99%